2004
DOI: 10.1002/star.200300195
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Digestibility of Raw Starches Extracted from five Yam (Dioscorea spp.) Species Grown in Jamaica

Abstract: Starch granules from Round leaf yellow yam, Negro yam, Sweet yam, Bitter yam and Chinese yam grown in Jamaica were isolated and characterized. The amylose content, granular size, crystallinity, and digestibility by α‐amylase were determined. The granules obtained were of three crystalline types. Round leaf yellow yam, Negro yam and Sweet yam were found to be type‐B, while Chinese yam and Bitter yam were type‐C and type‐A, respectively. Round leaf yellow yam had the highest amylose content (26.5%) while Chinese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 18 publications
5
53
0
Order By: Relevance
“…The variation in levels of nutrients and anti-nutritional factors observed among the varieties and field preparations may offer some meaningful information for taro cultivation and for further processing operations (Huang, Chen, & Wang, 2007). According to Riley et al (2004) the difference in amylose content observed may be attributed to genetic variations among the cultivars. In fact, it has been postulated that the amylose content of starches is affected by the expression of the amylose extender gene (Noda, Takahata, & Nagata, 1992).…”
Section: Amylose and Amylopectin Content Of Cocoyam Starchmentioning
confidence: 83%
“…The variation in levels of nutrients and anti-nutritional factors observed among the varieties and field preparations may offer some meaningful information for taro cultivation and for further processing operations (Huang, Chen, & Wang, 2007). According to Riley et al (2004) the difference in amylose content observed may be attributed to genetic variations among the cultivars. In fact, it has been postulated that the amylose content of starches is affected by the expression of the amylose extender gene (Noda, Takahata, & Nagata, 1992).…”
Section: Amylose and Amylopectin Content Of Cocoyam Starchmentioning
confidence: 83%
“…Physicochemical properties, such as percent light transmittance, amylose content, swelling power and water-binding capacity were significantly correlated with the average granule size of the starches separated from different plant sources (Singh et al, 2003 andZhou et al, 1998). The smaller granule sizes have been found to improve the digestibility because smaller granules have a greater surface area and are more rapidly digested by enzymes (Cone and Wolters, 1990, Franco et al, 1992and Riley, 2004. Apart from morphological properties, molecular structure of starches as obtained by size exclusion chromatography and/or fluorophore-assisted capillary electrophoresis is suggested.…”
Section: Semmentioning
confidence: 99%
“…Starches extracted from Jamaican yams have shown significant variations in their physical and chemical properties [3]. These differences in the starches physicochemical properties often tend to illicit variations in functional characteristics such as digestibility and crystallinity [3]. The variations in starch properties and botanical origin have also been shown to impact on the metabolic effects and the susceptibility of starch to a-amylase digestion [4].…”
Section: Introductionmentioning
confidence: 98%
“…Starches extracted from Jamaican yams have shown significant variations in their physical and chemical properties [3]. These differences in the starches physicochemical properties often tend to illicit variations in functional characteristics such as digestibility and crystallinity [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation